Prediction of the Lymph Node Status in Patients with Intrahepatic Cholangiocarcinoma: Analysis of 320 Surgical Cases - Chen, Yi-Xing; Zeng, Zhao-Chong; Tang, Zhao-You; Fan, Jia; Zhou, Jian; Jiang, Wei; Zeng, Meng-Su; Tan, Yun-Shan (Frontiers in Oncology, 2011)
Purpose: This study was conducted to identify factors involved in lymph node metastasis (LNM) and evaluate their role in predicting LNM in clinically lymph node negative (clinical stage I-III) intrahepatic cholangiocarcinoma (ICC). Materials and Methods: We selected 320 patients who were diagnosed with ICC with no apparent clinical LNM (T1-3N0M0). Age, gender, tumor boundary, histological differentiation, tumor size and CA19-9 value were the studied factors. Univariate and multivariate logistic analysis were conducted. Receiver operating characteristics (ROC) curve analysis was used to test the predicting value of each factor and a test which combined the associated factors was used to predict LNM. Results: LNM was observed in 76 cases (76/320, 23.8%). Univariate and multivariate analysis showed that histological differentiation as well as tumor boundary and tumor size significantly correlated with LNM. The sensitivity and negative predictive value (NPV) for LNM for the three factors when combined was 96.1% and 95% respectively. This means that 5% of the patients who did not have the risk factors mentioned above developed LNM. Conclusions: This model used the combination of three factors (low-graded histological differentiation, distinct tumor boundary, small tumor size) and they proved to be useful in predicting lymph node metastasis in ICC with clinically lymph node negative cases. In patients with these criteria, lymph node dissection or lymph node irradiation may be omitted and such cases may also be good candidates for stereotactic body radiotherapy (SBRT).